Outline Of The Development Of Military Criminal Law In Indonesia - Misdin Arifin HM; Dian Safitri Ginting (AT-TAFAHUM: Journal of Law, 2025)
This study aims to examine the broad development of military criminal law in Indonesia using normative legal research methods. The approaches employed include legislative and historical approaches to trace the dynamics of military criminal law regulation from the colonial period to the modern era. The results indicate that military criminal law in Indonesia was initially an adoption of the Dutch colonial legal system, which was then maintained and adapted after independence. Over its development, military criminal law has undergone a transformation toward a more modern national legal system while retaining its distinctive characteristics as an instrument for enforcing discipline in the military environment. However, this development also faces various challenges, such as the dualism between military criminal law and general criminal law and the suboptimal updates to the Military Criminal Code (KUHPM). Furthermore, there is a need to align military criminal law with the principles of the rule of law, transparency, and human rights protection. Therefore, efforts to reform regulations and harmonize laws are needed to create a more effective, just, and accountable justice system. This research is expected to contribute to the development of military criminal law in Indonesia and serve as a reference for further research.